A computational study for biological flapping wing flight - Kamakoti, R.; Berg, M.; Ljungqvist, D.; Shyy, Wei (2000)
A computational model for unsteady aerodynamics of a flapping wing has been developed based on the strip theory, which makes use of the concept of dividing the wing into a number of thin strips. This enables us to study the wing as a set of airfoils next to one another by assuming no crossflow between them. Wing kinematics including normal and chordwise force calculations was considered to calculate average lift, thrust, power requirements and propulsive efficiency for a flapping wing in flight. In addition, an optimization procedure was developed for obtaining maximum propulsive efficiency within the range of possible flying conditions. Computations were performed on a mechanical flying Pterosaur replica as well as smaller biological species including the Corvus monedula, Larus canus and Columba livia, which makes use of the vortex gaits. The effect of aerodynamic parameters on the performance of these biological flight vehicles was studied. It was found that the propulsive efficiency of all species considered were around 65-75% whereas the lift and thrust varied largely depending on the weight, flapping frequency and flight speed of the species. The range of dynamic twist for sustainable flying conditions (Lift > Weight) also varied for different species, becoming smaller as the size of a bird increases.